2002
DOI: 10.1210/jcem.87.6.8530
|View full text |Cite
|
Sign up to set email alerts
|

Nine Novel Mutations in Maturity-Onset Diabetes of the Young (MODY) Candidate Genes in 22 Spanish Families

Abstract: The aims of this study were to estimate the prevalence of major maturity-onset diabetes of the young (MODY) subtypes in Spanish MODY families and to analyze genotype-phenotype correlations. Twenty-two unrelated pediatric MODY patients and 97 relatives were screened for mutations in the coding region of the glucokinase (GCK), hepatic nuclear factor- HNF-1alpha and HNF4alpha genes using PCR-single strand conformation polymorphism and/or direct sequencing. In families carrying GCK mutations, the influence of gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
34
1
3

Year Published

2003
2003
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(43 citation statements)
references
References 33 publications
5
34
1
3
Order By: Relevance
“…In contrast to HNF-1a and GCK mutations, HNF-4a gene mutations are relatively uncommon worldwide [5,8,14,[17][18][19]. We found one single base substitution variant, T130I, in this study.…”
Section: Discussionmentioning
confidence: 46%
See 1 more Smart Citation
“…In contrast to HNF-1a and GCK mutations, HNF-4a gene mutations are relatively uncommon worldwide [5,8,14,[17][18][19]. We found one single base substitution variant, T130I, in this study.…”
Section: Discussionmentioning
confidence: 46%
“…However, in France [9], the prevalence of MODY2 is 56% of MODY suspected families, higher than in MODY suspected families in Spain (25%) [12], Japan (1%) [13] and China (3%) [8]. Furthermore, prevalences in the same country have differed depending on the method of recruitment of the proband; in Spain, HNF-1a/MODY3 mutations were observed in 18% and 35% of families according to whether the proband was a child or an adult [12,14].…”
Section: Discussionmentioning
confidence: 98%
“…A previous study has showed that the frequencies of the same mutation were 2.0% (2/100) and 0% (0/100) in Japanese Type 2 diabetic and control subjects, respectively [13]. Combining the results of these two Japanese studies indicates that the T130I mutation is more strongly associated with [18,19,20,21,22,23,24,25,26]. The mean age at diagnosis was higher for patients with the T130I mutation (47.1±8.8 years, p=1.0×10 −6 ) than for those with other HNF-4α mutations.…”
Section: Resultsmentioning
confidence: 91%
“…Developmental: primary endoderm, liver, kidney, pancreas, stomach, intestine; adult: HNF␣-1 and -2-liver (hepatocytes), kidney, small intestine and colon but not in the pancreas; HNF␣-3 and -4-liver; HNF␣-7-pancreas, adult liver, small intestine, colon, stomach but not in the liver {Hs, Mm, Rn} ͓Northern blot, in situ hybridization, Western blot, immunohistology͔ 4,[35][36][37] Functional assays Measurement of receptor activity using CAT and luciferase reporter genes in HeLa, HepG2, Hep3B, Saos2, Caco-2, and HEK 293 cells {Hs} 4,28,38 ; ectopic overexpression of HNF-4␣ in fibroblasts induces a mesenchymal-to-epithelial transition, indicating that HNF-4␣ is a dominant regulator of the epithelial phenotype {Mm} 39 Mutant phenotype Targeted disruption of the HNF-4␣ gene results in embryonic lethality; the embryos initiate but do not complete gastrulation in the absence of HNF-4␣ {Mm} ͓knockout͔ 48,49 ; adult mice lacking hepatic HNF-4␣ expression accumulated lipid in the liver and exhibited greatly reduced serum cholesterol and triglyceride levels and increased serum bile acid concentrations {Mm} ͓knockout͔ 39,50,51 ; mice lacking HNF-4␣ in pancreatic ␤ cells have hyperinsulinemia and, paradoxically, impaired glucose tolerance, as well as impaired glucose-stimulated insulin secretion and dysfunction of the K ATP channel activity {Mm} ͓conditional knockout͔ 52,53 Human disease Early-onset type 2 diabetes: due to the three SNPs (Asp 126 3Tyr, Asp 126 3His, Arg 154 3Gln) 54 ; late-onset type 2 diabetes: due to missense mutations in the LBD and F domain and 13 SNPs in the P2 promoter [55][56][57][58] ; MODY1: caused by mutations in several different human populations affecting either the DBD or LBD 32,[59][60][61][62][63] ; factor VII deficiency: caused by mutations in the HNF-4␣-binding site in the blood coagulation factor VII gene 64 ; hemophilia B Leyden: caused by mutations in the HNF-4␣-binding site in the blood coagulation factor IX gene [65][66][67] Biologically important isoforms TAk1 {Hs}; TR4a1 {Hs, Rn}: differ...…”
Section: Tissue Distributionmentioning
confidence: 99%